Biogeography of Micronekton Assemblages in the Natural Park of the Coral Sea - Receveur, Aurore; Vourey, Elodie; Lebourges-Dhaussy, Anne; Menkes, Christophe; Ménard, Frédéric; Allain, Valerie (Frontiers in Marine Science, 2020)
Mesopelagic resources are central to the ecosystem but remain poorly studied mainly due to the lack of observations. This paper investigated the assemblages of micronekton organisms and their habitat in the Natural Park of the Coral Sea around New Caledonia (southwest Pacific) using data from 141 pelagic trawls. A total of 67 130 micronekton individuals (fish, crustaceans, and molluscs) were collected, with 252 species identified, among 152 genus and 76 families. In the analyses we focused on 22 species, each were present in more than 33 trawls (i.e., in more than 25% of the total number of trawls) and studied their spatial distribution and vertical dynamic behaviour. Community structure was investigated through Region of Common Profile (RCP), an innovative statistical multivariate method allowing to study both species assemblages and environmental conditions influence on species occurrence probability. Nine major assemblages were identified, mainly driven by time of the day and sampling depth. Environmental variables such as mean oxygen concentration, mean temperature and bathymetry, also influenced micronekton assemblages, inducing a north/south distribution pattern. Three major day-assemblages were identified, distributed over the whole EEZ but segregated by depth: one assemblage in waters shallower than 200m and the other two in deeper waters, respectively in the north and the south. The night-assemblages were mostly segregated by depths, with two community changes at approximately 80m and 200m, and spatially with a north-south gradient. The predominant northern night assemblages were dominated by crustacean whereas the southern assemblage mostly by cephalopods and fish species. Generally, the southwest part of the EEZ was the most diverse part. Statistical analyses allowed to predict the spatial distribution of each species and their vertical migration behaviour was determined. Based on results, three important areas were identified to be considered for special management measures as part of the Natural Park of the Coral Sea.